2021
DOI: 10.2147/idr.s302195
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Giant Condyloma Acuminatum with Monotherapy of Topical Traditional Chinese Medicine: Report of Eight Cases

Abstract: Background: Giant condyloma acuminatum (GCA), also called Buschke-Löwenstein tumor, presents as a verrucous infiltrating lesion and is caused by sexual transmission of human papilloma virus. The optimal treatment is controversial and there are no standard guidelines because of its rarity and frequent recurrence. It has a relatively high local recurrence rate. Objective: We here report eight patients (six men and two women) with GCA whose lesions were successfully treated topically with traditional Chinese medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is composed of many ingredients, including Java brucea fruit oil, folium isatidis, spreading hedyotis herb, sophora flavescens and cnidium fruit. 8 Folium isatidis has a broad-spectrum antibacterial and antiviral effect. Java brucea has high selectivity for infected https://doi.org/10.2147/CCID.S400677…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is composed of many ingredients, including Java brucea fruit oil, folium isatidis, spreading hedyotis herb, sophora flavescens and cnidium fruit. 8 Folium isatidis has a broad-spectrum antibacterial and antiviral effect. Java brucea has high selectivity for infected https://doi.org/10.2147/CCID.S400677…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that topical use of traditional Chinese medicine preparation paiteling helps treat CA with satisfactory outcomes. 8 We report herein a case of an adult with giant CA around the anus and multiple condylomatous lesions on the penis, who also suffered from mixed hemorrhoid and IgA nephropathy meanwhile, successfully cured with external application of Chinese medicine preparation paiteling.…”
Section: Introductionmentioning
confidence: 97%